i'm giving u the general formula
derivative of x^n=nx^(n-1)
then, x^(1/3)
=1/3. x^(1/3 -1)
=1/3. x^(-2/3)
2006-12-06 10:28:58
·
answer #1
·
answered by niel_alinda 3
·
0⤊
0⤋
The 3 is just a constant and can be ignored until the end. Also the deriv of root of x is NOT x^(-1/2), it is x^(-1/2)*(1/2). I learned it as the root of x is 1 over 2 root x. It is just like x^2. To find its deriv, you just put the exponent in front and subtract 1. It is 2x^(2-1)=2x. So the deriv of x^(1/2) is just (1/2)x^(-1/2). Then at the end multiply that by 3.
2006-12-06 18:26:51
·
answer #2
·
answered by Michael W 2
·
0⤊
0⤋
One thing that derivatives, integrals, and limits have in common are that you can always ignore the constant
For instance, if
f(x) = 7x^2, then f'(x) = 7(2x) = 14x, and if
f(x) = 6sinx, then f'(x) = 6cosx
It's no different here. If f(x) = 3*x^(1/2), then f'(x) = 3 [(1/2)x^(-1/2)], or, if you want to simplify
f'(x) = 3 / [ 2 x^(1/2) ]
(It's proper mathematical etiquette not to have negative exponents, though you're unlikely to lose marks over that on a Calculus test)
2006-12-06 18:26:45
·
answer #3
·
answered by Puggy 7
·
0⤊
0⤋
are you talking about the 3 in front of the x or in front of the negative 1/2
2006-12-06 18:28:44
·
answer #4
·
answered by Danny 1
·
0⤊
0⤋
Root x is x^(1/2), not x^(-1/2).
d/dx 3x^(1/2) = (3/2) x^(-1/2)
The answer is 3/(2 sqrt(x)).
2006-12-06 18:25:55
·
answer #5
·
answered by computerguy103 6
·
0⤊
0⤋
root(x) = x^(1/2), not x^(-1/2)
3sqrt(x) = 3x^(1/2)
the derivative of this is
(3/2)x^((1/2) - 1)
(3/2)x^(-1/2)
3/(2sqrt(x))
3/(sqrt(4x))
(3sqrt(4x))/(4x)
(6sqrt(x))/(4x)
(3sqrt(x)/(2x)
ANS : (3sqrt(x))/(2x)
2006-12-06 20:45:07
·
answer #6
·
answered by Sherman81 6
·
0⤊
0⤋